The Effect of the Implementation of Academic Supervision and Pedagogic Competition on the Performance of Science Teachers in Junior High School South Parigi Sub-District - Indriana, Rinny; Tellu, Andi Tanra; Ramadhan, Achmad (Universitas Tadulako, 2018)
The research aims to analyze the effect of the implementation of the academic supervision on the performance of junior high school science teacher in the District of South Parigi, analyze the effect of pedagogical competence on the performance of junior high school science teacher in the District of South Parigi, and analyze the effect of implementation supervision of academic and pedagogical competence on the performance of junior high school science teacher in the District of South Parigi. The method employed was quantitative descriptive, with a population sampling technique or sampling saturated. The Variable observation is the implementation of the academic supervision, pedagogical, and the performance of teachers conducted by the supervisor. The research result indicated that the implementation of the academic supervision conducted by supervisors was no real effect on the performance of teachers, pedagogical competence possessed by the teachers' real influence the performance of teachers, and the implementation of academic and pedagogic supervision simultaneously real effect on the performance of teachers.